2004
DOI: 10.1111/j.1447-0349.2004.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Clients’ perceptions of client−nurse relationships in local authority psychiatric services: A qualitative study

Abstract: The Mental Health Care reform in Sweden aimed, among other things, to improve the possibilities for persons with mental illnesses to experience companionship and participation in society. The aim of the study was to describe how persons suffering from mental illness perceive their relationships with nursing staff in local authority psychiatric services. Data were collected through semi-structured recorded interviews with 17 strategically chosen clients. A qualitative approach inspired by phenomenography was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…A caring relationship is based on compassion, respect, and a non-judging attitude. Previous research has also described how psychiatric inpatients valued a communicative, empathetic and available staff (Hörberg et al, 2004;Salzmann-Eriksson, Lützen, Ivarsson, & Eriksson, 2008). For example, the patients preferred that staff members work proactively and become involved at an early stage in aggressive incidents to prevent the situation from intensifying (Meehan et al (2006).…”
Section: Discussionmentioning
confidence: 93%
“…A caring relationship is based on compassion, respect, and a non-judging attitude. Previous research has also described how psychiatric inpatients valued a communicative, empathetic and available staff (Hörberg et al, 2004;Salzmann-Eriksson, Lützen, Ivarsson, & Eriksson, 2008). For example, the patients preferred that staff members work proactively and become involved at an early stage in aggressive incidents to prevent the situation from intensifying (Meehan et al (2006).…”
Section: Discussionmentioning
confidence: 93%
“…However, when nurses are socialized into a context where patients are presented as potentially dangerous, they tend to distance themselves from patients (Jacob & Holmes 2011). A distant position can block nurses' understanding of patients' expressions of suffering, so that instead of facilitating patients' understanding of and reconciliation with suffering, they might focus on restrictions and fostering interventions (Hörberg et al 2004, Martin & Street 2003. The nurse-patient relationship is also challenged when nurses need to carry out interventions -for instance, implementing restrictions -in order to protect the patient and other persons from harm.…”
Section: Introductionmentioning
confidence: 99%
“…If nurses lack patience and understanding in such situations, patients adjust their behaviour in order to gain benefits (Hörberg et al 2012) and hide their suffering for fear of misunderstanding and rejection (Hostick & McClelland 2002). Not being able to express suffering verbally also contributes to the development of destructive emotions (Carlén & Bengtsson 2007) and to a perception of the nurse as a guard rather than a caregiver (Hörberg et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, trust is a major criterion for developing good therapeutic relationships (Horberg, Brunt, & Axelsson, 2004;Videbeck, 2011). Good relationships were reported by the participants, who suggested that communication to seek approval from patients is required for good relationships to develop.…”
Section: Discussionmentioning
confidence: 99%